The impact of weight loss among seniors on Medicare spending - Kenneth E. Thorpe; Zhou Yang; Kathleen M. Long; W. Timothy Garvey (Health Economics Review, 2013)
Objective: To examine the impact of temporary and permanent weight loss of 10% and 15% on 10-year and lifetime Medicare spending among adults with overweight and obesity aged 65 years and older. Weight loss of this magnitude is consistent with next generation anti-obesity medications recently approved by the Food and Drug Administration. Methods: We follow the approach of a longitudinal dynamic aging process model developed by our research team. This model considers the dynamic relationships between weight, chronic disease, acute medical events, functional status, mortality, health care utilization and spending among Medicare beneficiaries from age 65 until death. Using this model, we estimate baseline Medicare spending over the next decade and then over the lifetime of seniors with a body mass index (BMI) Ï 27 with at least one weight-related comorbidity (overweight), and seniors with obesity having a BMI Ï 30 and Ï 35. We then estimate Medicare spending for this population between ages 65 and 70 over the course of a year, assuming 10% and 15% weight loss under alternative scenarios: with and without weight regain. (Weight regain is assumed to be 90% over a 10-year period.) The difference in spending between baseline (no weight-loss intervention) and the alternative scenarios represent potential gross savings to the Medicare program. Results: Permanent weight loss of 10 to 15% will yield 9,445 to 15,987 in gross per capita savings throughout their lifetime, and 8,070 to 13,474 over ten years. Similarly, initial weight loss of 10 to 15% followed by 90% weight regain will result in gross per capita savings of 7,556 to 11,109 over their lifetime, and 6,456 to 8,911 over ten years. Targeting weight loss medications to adults with obesity (BMI Ï 30) produces greater savings to the Medicare program. Conclusion: Medicare can realize significant cost savings through anti-obesity medications that produce substantial weight loss, and as a result, reduce the progression to type 2 diabetes, and improve blood pressure and glycemic indicators in hypertensive and diabetic patients, respectively. Medications are currently excluded from coverage in the Medicare program, however, in light of potential savings and health benefits, may warrant consideration.
Keywords: 330